Osteoarthritis year in review 2017: biology. Issue 3 (March 2018) - Appleton, C.T.
Summary: This Year in Review was derived from a personal selection of articles investigating biological mechanisms of osteoarthritis (OA) and presented at the OARSI World Congress on April 30, 2017. Selected articles were published between the March, 2016 and April, 2017 OARSI meetings. PubMed/MEDLINE searches were performed using the terms "osteoarthritis", "cartilage", "subchondral bone", "synovium", "synovitis", and "ageing". Biomechanical, genetic, genomic, epigenomic, biomarker, clinical, imaging, and tissue engineering studies were excluded since they are covered by other articles in this series. Several new and emerging themes were identified. Incorporating new technologies such as designer genetic engineering, nanotechnology, and bio-selective nuclear medicine tracers into study designs helps to gain important insights into OA pathophysiology. Potentially critical differences exist between biological mechanisms of post-traumatic, age-associated, and metabolic phenotypes of OA. The concept of OA stages is highlighted, demonstrating how this may influence which biological mechanisms are at play and the need for strategic timing of treatment interventions. Not all inflammation is bad and fine-tuning a balance within inflammatory signaling mechanisms may be a path to regain joint homeostasis. Not only is the joint an organ system, sub-regions within each joint tissue, especially the joint lining, may play distinct roles in damage and repair. To accompany the review, the interaction among studies spanning multiple areas is summarized schematically.